2017
DOI: 10.1080/07294360.2017.1325854
|View full text |Cite
|
Sign up to set email alerts
|

Peer feedback on college students’ writing: exploring the relation between students’ ability match, feedback quality and essay performance

Abstract: There does not appear to be consensus on how to optimally match students during the peer feedback process: with same-ability peers (homogeneously) or different-ability peers (heterogeneously). In fact, there appears to be no empirical evidence that either homogeneous or heterogeneous student matching has any direct effect on writing performance. The current study addressed this issue in the context of an academic writing task. Adopting a quasi-experimental design, 94 undergraduate students were matched in 47 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
(40 reference statements)
3
28
1
Order By: Relevance
“…Our results expand on results found by Huisman et al (2017Huisman et al ( , 2018 who found that the nature of received peer feedback was not related to students' writing improvement and that students' peer feedback perceptions were not related to an increase in writing performance. The current study applied the same coding scheme to identify the nature of peer feedback and used the same questionnaire for feedback perceptions, but in the context of a presentation assignment.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results expand on results found by Huisman et al (2017Huisman et al ( , 2018 who found that the nature of received peer feedback was not related to students' writing improvement and that students' peer feedback perceptions were not related to an increase in writing performance. The current study applied the same coding scheme to identify the nature of peer feedback and used the same questionnaire for feedback perceptions, but in the context of a presentation assignment.…”
Section: Discussionsupporting
confidence: 84%
“…Following earlier research (van den Berg, Admiraal, and Pilot, 2006;Huisman et al 2017) on peer feedback comments, the comments and annotations were coded using feedback functions (analysis, evaluation, revisions, and possible elaborations on the final two) and feedback aspects (in this case the four main categories of the rubric: content, speech, presence and audio-visual tools). Each fragment was coded using a matrix of the functions and aspects, and the number of comments in each category was counted and used for analysis.…”
Section: Peer Feedbackmentioning
confidence: 99%
“…Coding procedure. Following the two-step procedure used by Huisman et al (2017), feedback segments were first coded as an aspect of content, structure or style, after which each aspect-coded segment was assigned one or more feedback functions. Hence, a feedback segment was attributed only one feedback aspect, which could include multiple functions.…”
Section: The Nature Of Peer Feedbackmentioning
confidence: 99%
“…Function-related feedback types refer to the role that feedback serves concerning the text. This type of feedback has been categorized into analysis, evaluation, explanation, and revision (Van den Berg et al, 2006 ; Van der Pol et al, 2008 ; Huisman et al, 2017 , 2018 ). Others have classified feedback as cognitive or affective; they have identified cognitive feedback categories of summarization, specificity, explanation, and scope and affective feedback categories of praise and mitigation language (Nelson and Schunn, 2009 ; Patchan and Schunn, 2015 ; Patchan et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, each type has been found to have a significant influence on writing. Summary and praise have been found to be positively associated with feedback implementation (Bienstock et al, 2007 ; Nelson and Schunn, 2009 ); problems and solutions have been found to have inconsistent results regarding their relationships with writing across different studies (Tsui and Ng, 2000 ; Tseng and Tsai, 2007 ; Bitchener, 2012 ; Huisman et al, 2017 ). These inconsistent results may be attributed to students' varying writing proficiencies.…”
Section: Literature Reviewmentioning
confidence: 99%